Active variable stiffness system with non-resonant control. - Nasu, Tadashi (Earthquake engineering & structural dynamics.)
The active variable stiffness (AVS) system is proposed as a seismic response control system. It actively controls structural stiffness of a building to establish a non-resonant state against earthquake excitations, thus suppressing the building's response. It consumes a relatively small amount of energy and maintains the safety of the building in moderate to severe earthquakes. In order to accumulate and analyse practical data, a building was constructed as a trial structure about ten years ago. This paper describes the control algorithm, the applied system, some observed earthquake records, verification of control effectiveness based on simulation analyses, and some issues concerning system maintenance. Through earthquake observations, it was confirmed that the system could select the appropriate stiffness that assures a non resonant state, which results in a minimum response.